Konsumsi/pengeluaran rumah tangga, sosial budaya, lingkungan dan kesehatan Propinsi Sumatera Barat, 1981 (Survei sosial ekonomi nasional., 1983)
Consumption and expenditure statistics of households in the socio-cultural, environment, and health sectors in West Sumatra.